PEMERIKSAAN TROMBOSIT, HEMATOKRIT, DAN LEKOSIT PADA PENDERITA SUSPEK DEMAM BERDARAH DENGUE (DBD) - Faikotuljannah Faikotuljannah; Titik Sundari; Muhammad Sungging Pradana (Faculty of Health Sciences Universitas Maarif Hasyim Latif, 2022)
Dengue Haemorrahagic Fever (DHF) is an acute epidemic disease caused by the dengue virus that spreads rapidly throughout the world, especially in tropical and subtropical areas (WHO, 2014). In dengue hemorrhagic fever, plasma seepage occurs which is characterized by hemoconcentration (increased hematocrit) or fluid accumulation in the body cavity. This study aims to determine the number of hematocrit and leukocytes of patients with suspected dengue hemorrhagic fever (DHF) with thrombocytopenia. It was concluded that as many as 25 samples, 10 samples of leukocyte values were below normal (40%) and 15 samples did not experience a decrease (60%). The hematocrit obtained 8 samples below normal (32%) and 17 samples with normal hematocrit (68%) the lowest value was 25.4% and the highest was 48.1%.